2014
DOI: 10.5194/angeo-32-1073-2014
|View full text |Cite
|
Sign up to set email alerts
|

Waves off Gopalpur, northern Bay of Bengal during Cyclone Phailin

Abstract: Abstract. The wave statistical parameters during Cyclone Phailin which crossed the northern Bay of Bengal are described based on the Directional Waverider buoy-measured wave data from 8 to 13 October 2013. On 12 October 2013, the cyclone passed within 70 km of the Waverider buoy location with a wind speed of 59.2 m s −1 (115 knots), and during this period, a maximum significant wave height of 7.3 m and a maximum wave height of 13.5 m were measured at 50 m water depth. Eight freak wave events are observed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Gopalpur located along the northwestern part of the BoB is influenced by TC (Amrutha et al ., ). Maximum SWH of 7.3 m and maximum wave height of 13.5 m is measured at 50 m water depth off Gopalpur during TC Phailin in 2013 (Amrutha et al ., ). Anjali Nair et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gopalpur located along the northwestern part of the BoB is influenced by TC (Amrutha et al ., ). Maximum SWH of 7.3 m and maximum wave height of 13.5 m is measured at 50 m water depth off Gopalpur during TC Phailin in 2013 (Amrutha et al ., ). Anjali Nair et al .…”
Section: Introductionmentioning
confidence: 99%
“…Gopalpur located along the northwestern part of the BoB is influenced by TC (Amrutha et al, 2014). Maximum SWH of 7.3 m and maximum wave height of 13.5 m is measured at 50 m water depth off Gopalpur during TC Phailin in 2013 (Amrutha et al, 2014). Anjali Nair et al (2018) observed that a single TC influenced the annual maximum SWH off Gopalpur, but the annual average SWH value is almost same (~1 m) in years with TC (in 2014) and without TC (in 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Observational wave data in the BoB are sparse. Only few wave buoy records exist, and these are intermittent (Sanil Kumar et al, , ; Suresh et al, ; Johnson et al, ; Amrutha et al, ; Patra et al, ). Sanil Kumar et al .…”
Section: Introductionmentioning
confidence: 99%
“…Observational wave data in the BoB are sparse. Only few wave buoy records exist, and these are intermittent (Sanil Kumar et al, 2001Suresh et al, 2010;Johnson et al, 2013;Amrutha et al, 2014;Patra et al, 2016). Sanil reported that the seasonal average value of significant wave height (SWH) varied from 0.8 m in the northeast (NE) monsoon season (ONDJ) to 1.3 m in the southwest (SW) monsoon season (JJAS) along the northwestern BoB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation